Awl Nematodes, Dolichodorus spp. Cobb, 1914 (Nematoda: Secernentea: Tylenchida: Tylenchina: Dolichodoridae: Dolichodorinae) - William T. Crow; Angela S. Brammer (EDIS)
Awl nematodes were first described in 1914 from specimens collected at Silver Springs, Florida, and Douglas Lake, Michigan. Species of Dolichodorus are found worldwide, but two species, D. heterocephalus and D. miradvulvus, are the most common in Florida. Usually, awl nematodes are found in moist to wet soil, low areas of fields, and near irrigation ditches and other bodies of fresh water. Because these nematodes prefer moist to wet soils they rarely occur in agricultural fields and are not as well studied as many other plant-parasitic nematodes. This document is EENY-241, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: September 2001.